Analisis Peran Manajer Lapangan dalam Optimalisasi Manajemen Sumber Daya Manusia pada Proyek Konstruksi di Kota Malang - Kartika Dian Rahmawati; Dafid Irawan; Riman Riman (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This research looks into how site managers in construction projects in Malang City manage and improve their use of human resources. The research is driven by the significance of effective human resource management in ensuring project success and the lack of studies focusing on the operational strategies of site managers within a local context. This study uses a quantitative method that is both descriptive and analytical. It involves giving out a survey to 40 people, including site managers, contractors, and foremen. The independent variables include leadership and supervisory style, human resource planning and workforce allocation, training and competency development, team communication and coordination, performance monitoring and evaluation, as well as motivation and welfare. The dependent variable is the degree to which human resource management is optimized. The results of validity and reliability tests indicate that all research instruments are valid and reliable. Multiple linear regression analysis shows that leadership and supervisory style, along with human resource planning and workforce allocation, have a significant partial effect on improving HRM practices. Other variables have a positive but statistically insignificant partial effect on the estate. Overall, the management of human resources in construction projects in Malang City is considered to be fairly good. This study confirms that leadership and workforce planning are the main strategic factors for site managers in improving the effectiveness of human resource management in construction projects.